The Role of Fisheries Extension Officers in Empowering Fishermen Groups in Sumpang Binangae Village, Barru Regency - Febri Yanti Panjaitan; Benny Audy Jaya Gosari; Firman Firman; Sitti Fakhriyyah; Endah Murpi Ningrum (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2025)
Fisheries extension officers play a strategic role in empowering and developing fishermen's groups toward sustainable and productive agribusiness. This study aims to evaluate the roles of fishery extension officers as facilitators, communicators, and motivators, as well as to identify key challenges in the development of fishermen groups in Sumpang Binangae Village and Barru Regency. A descriptive quantitative approach was applied, with data collected through observations, interviews, documentation, and questionnaires involving 18 respondents from three groups of fishermen. The results indicated that the extension officer’s role as a facilitator was perceived as “active” by 66.7% of respondents, as a communicator “very active” by 72.2%, and as a motivator “active” by 55.6%. The main challenges included a limited number of extension personnel, time constraints of fishermen, and lack of extension facilities and tools. These findings highlight the need to strengthen extension institutions through participatory, integrated, and community-based approaches to improve the effectiveness of fishery agribusiness development at the grassroots level.